Mechanical and nuclear radiation shielding properties of different boro-tellurite glasses: a comprehensive investigation on large Bi2O3 concentration. (19th June 2020) - Gaballah, Mahmoud; Issa, Shams A M; Saddeek, Yasser B; Elsaman, Reda; Susoy, G; Erguzel, T T; Alharbi, Thamer; Tekin, H O
Abstract: In this study, the synergistic positive effect of Bi2 O3 additive on protective glasses with high efficiency against gamma and neutron is underlined. Five different boro-tellurite glass samples coded as BTB40, BTB50, BTB60, BTB70, and BTB80 were produced. These glasses have been examined for their rigidity and radiation shielding properties. The mass attenuation coefficients ( μ m ) of these glass samples in the energy range of 0.015 MeV to 15 MeV have been calculated comparatively with the MCNP simulation and XCOM theoretical program. Half Value Layer (HVL), Tenth Value Layer (TVL), Mean Free Path (MFP), Effective Atomic Number (Zeff ), Energy Absorption Buildup Factors (EABF) at different penetration depths and Effective Removal section (ΣR ) (for fast neutrons) known as important shielding parameters were calculated for boro-tellurite glass samples. Along with the nuclear radiation shielding parameters, several mechanical properties of the glass samples the longitudinal (L), shear (G), bulk (K), Young's (Y) modulus were calculated with the help of Shear ultrasonic velocity (Vs ) ultrasonic velocities, Longitudinal ultrasonic velocities (VL ) and density ( ρ ). Among the mentioned shielding parameters; low HVL, TVL, MFP, EABF and high μ m, Zeff, ΣR values show that the glass material has good shielding properties. According to the results obtained, BTB80 glass sample with the highest Bi2 O3 additive showed excellent nuclear radiation shielding and elastic properties among other glass samples.